Comprehending adsorption of methylethylketone and toluene and microwave regeneration effectiveness for beaded activated carbon derived from recycled waste bamboo tar. (2nd June 2020) - Chen, Yu-Ting; Huang, Ying-Pin; Wang, Can; Deng, Ji-Guang; Hsi, Hsing-Cheng
ABSTRACT: Beaded activated carbons (BACs) were derived from waste bamboo tar through carbonization (500°C for 2 hr) followed by physical activation using carbon dioxide (800–900°C for 2–4 hr). The adsorbent was examined for their physical and chemical properties, adsorption capacities toward methylethylketone (MEK) and toluene, and regenerabilities under microwave heating. It was found that the maximum total surface area reached for bamboo-tar-derived BAC after physical activation was 1364 m 2 g −1, and more than 95% of the area was attributed to the microporous structures. Langmuir, Freundlich, and Dubinin-Radushkevich (D-R) isotherm models were applied to the adsorption isotherm fitting, and the minimum R 2 for each model was 0.986, 0.915, and 0.943, respectively. The isosteric heats of adsorption calculated based on D-R parameters for methylethylketone and toluene were 44.04 to 51.50 and 45.88 to 73.27 KJ mol −1, respectively. They were slightly over the range of physisorption and increased with adsorbate loading, which might be related to the micropore filling mechanism. Microwave regeneration under 600 W of power output removed most of the adsorbate (>93.03%) within 8 min. The results of this study are intended to benefit future study on waste-derived adsorbent in environmental applications. Implications: Recycling waste bamboo tar for the novel adsorbent preparation is shown feasible in this study. Beaded activated carbon (BAC) synthesized from this waste bamboo tar possessed a high specific surface area, which aided in the capturing of volatile organic compounds (VOCs). Three adsorption isotherms, Langmuir, Freundlich, Dubinin-Radushkevich (D-R) models can be applied in interpreting the experimental adsorption data, providing information on adsorption heat and possible adsorption mechanism. A potential microwave regeneration method for BAC is tested, showing high desorption efficiencies with minimum heel formation. These findings can provide a new pathway for waste bamboo tar management and VOC abatement using adsorbents.